EDUKASI MASYARAKAT MELALUI PAMFLET SEBAGAI UPAYA PENCEGAHAN GIGI BERLUBANG DAN PENYAKIT MULUT - Kadek Dwi Dessy Sapitri; Hendri Poernomo; Ni Wayan Arni Sardi (LOKATARA SARASWATI, 2025)
Besakih Village, located in Rendang District, Karangasem Regency, Bali, is a culturally rich village known for Besakih Temple, the largest and holiest temple in Bali, which also serves as a major tourist attraction. However, observations reveal that the community still lacks adequate oral health awareness. The level of knowledge about dental diseases such as cavities and periodontal disease remains low, increasing the risk of oral health problems. To address this issue, a Social Service program was held in 2025 focusing on oral health care in Besakih Village. This program provided free dental treatments including scaling, cavity fillings, and tooth extractions. In addition to treatment, oral health education was conducted, covering dental anatomy, cavity care, and prevention of periodontal disease. Informational pamphlets on oral hygiene maintenance were distributed to the community. The program targeted children and the general population to improve knowledge and awareness of oral health maintenance. It is expected that through this Social Service activity, the oral health quality of Besakih Village residents will significantly improve.